Fluxes of carbon and nutrients to the Iceland Sea surface layer and inferred primary productivity and stoichiometry - Jeansson, Emil; Bellerby, Richard; Skjelvan, Ingunn; Frigstad, Helene; Ólafsdóttir, Sólveig R.; Ólafsson, Jón Hjaltalín (Biogeosciences, 2018)
This study evaluates long-term mean fluxes of carbon and nutrients to the upper 100 m of the Iceland Sea. The study utilises hydro-chemical data from the Iceland Sea time series station (68.00° N, 12.67° W), for the years between 1993 and 2006. By comparing data of dissolved inorganic carbon (DIC) and nutrients in the surface layer (upper 100 m), and a sub-surface layer (100–200 m), we calculate monthly deficits in the surface, and use these to deduce the long-term mean surface layer fluxes that affect the deficits: vertical mixing, horizontal advection, air–sea exchange, and biological activity. The deficits show a clear seasonality with a minimum in winter, when the mixed layer is at the deepest, and a maximum in early autumn, when biological uptake has removed much of the nutrients. The annual vertical fluxes of DIC and nitrate amounts to 2.9 ± 0.5 and 0.45 ± 0.09 mol m−2 yr−1, respectively, and the annual air–sea uptake of atmospheric CO2 is 4.4 ± 1.1 mol C m−2 yr−1. The biologically driven changes in DIC during the year relates to net community production (NCP), and the net annual NCP corresponds to export production, and is here calculated as 7.3 ± 1.0 mol C m−2 yr−1. The typical, median C : N ratio during the period of net community uptake is 9.0, and clearly higher than the Redfield ratio, but is varying during the season. publishedVersion